아밀로이드 베타(amyloid beta)로 유도된 인지장애 마우스 모델에서 갑주백목(Diospyros kaki) 추출물의 인지기능 및 뇌 신경세포 보호 효과 - 유슬기(Seul Ki Yoo); 김종민(Jong Min Kim); 박선경(Seon Kyeong Park); 강진용(Jin Yong Kang); 한혜주(Hye Ju Han); 박효원(Hyo Won Park); 김철우(Chul-Woo Kim); 이욱(Uk Lee); 허호진(Ho Jin Heo) (Han'guk Sikp'um Kwahakhoe Chi = Korean Journal of Food Science and Technology, 2019)
The current study investigated the effect of Gabjubaekmok (Diospyros kaki) ethanolic extract (GEE) on H2O2induced human neuroblastoma MC-IXC cells and amyloid beta (Aβ)1-42-induced ICR (Institute of Cancer Research) mice. GEE showed significant antioxidant activity that was evaluated based on ABTS, DPPH scavenging activity, and inhibition of malondialdehyde (MDA) and acetylcholinesterase activity. Further, GEE inhibited ROS production and increased cell viability in H2O2-induced MC-IXC cells. Administration of GEE ameliorated the cognitive dysfunction on Aβ-induced ICR mice as evaluated using Y-maze, passive avoidance, and Morris water maze tests. Results of ex vivo test using brain tissues showed that, GEE protected the cholinergic system and mitochondrial functions by increasing the levels of antioxidants such as ROS, mitochondrial membrane potential (MMP), and adenosine triphosphate (ATP) against Aβ-induced cognitive dysfunction. Moreover, GEE decreasd the expression levels of apoptosis-related proteins such as TNF-α, p-JNK, p-tau, BAX and caspase 3. While, expression levels of p-Akt and p-GSK3β increased than Aβ group. Finally, gallic acid was identified as the main compound of GEE using high performance liquid chromatography.